Speech act in the main character of “Luca” movie - Nurul Faizah; Dian Luthfiyati; Fita Faridah (Jurnal Penelitian Humaniora, 2022)
Language is very important in our life, because without language we cannot communicate with each other. In communication, language has an important role because with a language we can express what is on our mind. In this case, learning speech act theory becomes important to overcome this problem. Speech acts are actions that can be done through speech. The purpose of this study was to determine the types of speech acts performed by the main character and to determine the function of the speech acts performed by the main character in Luca's film through the script. speech acts are divided into three acts; locutionary acts, illocutionary acts, and perlocutionary acts. In this study, illocutionary acts are the most important speech acts and are related to what the speaker meant. The illocutionary acts are divided into five illocutionary speech acts; representative, directive, commissive, expressive, and declarative. In this study, the researcher found all illocutionary acts performed by the main character in Film luca through the script. And the illocutionary acts used by the main character in Luca's film through the script, the researchers found 113; 27 representative, 45 directive, 4 commissive, 34 expressive, and 3 declarative. The most common illocutionary act is the directive illocutionary act, which is often done by the main character in Luca's film through the script. In this study, the researcher used a qualitative descriptive method in the form of documents in the form of films and scripts to describe and analyze the speech acts selected in the script, then classify them according to the concept of John R. Searle's illocutionary acts. In this study, the researcher found that Luca performed all illocutionary acts: representative, directive, commissive, expressive, and declarative.Keywords: Speech Acts, Illocutionary Acts, Luca Film Script